CO2 Transport by Ship: The Way Forward in Europe. (July 2017) - Neele, Filip; de Kler, Robert; Nienoord, Michiel; Brownsort, Peter; Koornneef, Joris; Belfroid, Stefan; Peters, Lies; van Wijhe, Andries; Loeve, Daniel
Abstract: This paper presents the results of a study into the functional requirements and optimisation of the CO2 shipping chain, with a focus on the offshore offloading system. The goal was to evaluate the feasibility of a generic approach to the development of ship-based CO2 transport and storage systems in the North Sea, using a range of typical North Sea reservoirs (saline formations or depleted hydrocarbon fields). The feasibility of such a generic approach would help develop the ship transport option that is widely regarded as an important option for developing offshore CO2 storage (or enhanced recovery with CO2 ). This will be especially true in the first phase of CCS, when capture locations are few and at large distance from each other. In this phase ship transport is the best option to collect the captured CO2 and to deliver to one or two storage or enhanced recovery sites. The results provide insight into the requirements for offshore offloading from a ship into an injection well for a range of potential North Sea storage reservoirs. The results of the analysis are presented in terms of pumping and heating requirements (to bring the CO2 from the conditions in the ship to conditions acceptable for the injection well) and the required investment cost and operational cost of shipping CO2 .